A1.9 Among patients with venous thrombo-embolism, B cell subset disturbances characterise those with primary antiphospholipid syndrome. (13th February 2015) - Simonin, L; Pasquier, E; Leroyer, C; Cornec, D; Bendaoud, B; Hillion, S; Couturaud, F; Renaudineau, Y
Abstract : Background and objectives: Lymphocytes subset distribution is altered in numerous autoimmune diseases, and our aim was to evaluate lymphocyte distribution in well-characterised primary antiphospholipid syndrome (pAPS) patients selected from a venous thromboembolism (VTE) cohort. Materials and methods: Cases of pAPS VTE patients (n = 11) and matched non-APS VTE patients were selected during their follow-up from the data base EDITH (study of determinants interactions of venous thrombosis), which is a monocentric case-control cohort (n = 5, 539). In addition, matched autoimmune disease patients (Sjögren's syndrome and systemic lupus erythematosus) and controls were also included. Using a 4 colours flow cytometer, peripheral blood B cell subsets (B1, transitional, naïve, and memory), T cell subsets (CD3, CD4, CD8) and NK-cells were explored. Results: In contrast to non-APS VTE patients and controls, pAPS VTE patients displayed total CD3 and CD8 naïve (CD45RA + CD27 + ) T cell reduction, and disturbance in B cell homeostasis with increased proportions of B1 cells, transitional B cells (CD24 + + CD38 + + ) and naïve B cells, while memory B cells were reduced. The unswitch memory B cell percentage (IgD + CD27 + ), and even better the naïve (IgD + CD27 - )/unswitched memory B cell ratio were both effective to distinguish pAPS VTE patients from non-APS VTE patients, and from patients with autoimmune diseases. Moreover, the absolute number of CD4 T cells was positively correlated with IgG anti-cardiolipin antibody levels. Conclusions: Disturbances of B cell homeostasis characterised, within VTE patients, those with pAPS during their follow-up and an elevated naïve/unswitched memory B cell ratio represent a useful biomarker to characterise them.